Ablation of C9orf72 together with excitotoxicity induces ALS in rats. (24th August 2020) - Dong, Wei; Ma, Yuanwu; Guan, Feifei; Zhang, Xu; Chen, Wei; Zhang, Li; Zhang, Lianfeng
Abstract : Pathogenesis of familial amyotrophic lateral sclerosis (ALS) linked to expansion of the chromosome 9 open reading frame 72 ( C9orf72 ) hexanucleotide repeat that impairs C9orf72 expression. Loss of function of the C9orf72 protein is one of the three main proposed C9orf72 ‐related ALS mechanisms. However, C9orf72 loss of function, by itself, is insufficient to cause severe phenotypes in mice. Excitotoxicity is another major disease mechanism of ALS. We speculate that loss of C9orf72 protein might cause ALS in combination with excitotoxicity. To date, the effect of C9orf72 deficiency in the background of SD rat has not been examined. To test our hypothesis, we generated a line of rat with a deletion of part of the C9orf72 gene ablating the encoded protein. These animals did not develop any ALS phenotypes; however, when they were treated with kainic acid, an excitotoxicity inducer, the rats developed motor deficits and showed loss of motor neurons (MNs), Golgi complex fragmentation, and abnormal vesicle trafficking. RNA sequencing revealed profound changes in the gene profiles that were primarily associated with neural activity. Our results demonstrated that C9orf72 ablation alone was not enough to cause ALS pathogenesis in rat; but the ablation sensitized MNs to other risk factors that synergistically caused the ALS. These results support a loss of function of C9orf72 mechanism of ALS. Abstract : We generated a knockout rat line with C9orf72 protein ablation by CRISPR/Cas9. These animals did not develop any amyotrophic lateral sclerosis (ALS) phenotypes; however, once they were treated with low dose of kainic acid, an excitotoxicity inducer, the rats developed motor deficits, loss of motor neurons, Golgi complex fragmentation, and abnormal vesicle trafficking. These results support a loss of function of C9orf72 mechanism of ALS.